Repurposing Osimertinib and Gedatolisib for Glioblastoma Treatment: Evidence of Synergistic Effects in an In Vitro Phenotypic Study - Vitória Santório de São José; Bruno Marques Vieira; Vivaldo Moura Neto; Lidia M. Lima (Pharmaceuticals)
Background/Objectives: Glioblastoma is a malignant tumor with a poor prognosis for the patient due to its high lethality and limited chemotherapy available. Therefore, from the point of view of chemotherapy treatment, glioblastoma can be considered an unmet medical need. This has led to the investigation of new drugs for monotherapy or associations, acting by synergistic pharmacological mechanisms. Methods: Here, we propose the combination of Osimertinib (a potent EGFR inhibitor) and Gedatolisib (a potent PI3K/mTOR dual inhibitor) through an in vitro phenotypic study using five human GB lines and establish the cytotoxic potency, selectivity, and effect on proliferation, apoptosis, and cell cycle by simultaneously inhibiting EGFR, PI3K, and mTOR. Results: Cytotoxic potency of Gedatolisib and Osimertinib in the selected GB cell lines was determined, which highlighted the synergistic response from their combination and its impact on migration reduction, G0/G1 cell cycle arrest, GB cytotoxicity, and apoptosis-inducing effects for different GB cell lines. Conclusions: From the drug combination studies in phenotypic in vitro models, it was possible to suggest a new potential treatment for glioblastoma that justifies further safe in vivo phases of preclinical trials with the combination.